Stimuli-responsive drug delivery systems for head and neck cancer therapy - Jingou Liang; Bina Yang; Xuedong Zhou; Qi Han; Jing Zou; Lei Cheng (Taylor & Francis Group, 2021)
Head and neck cancer (HNC) is among the most common malignancy that has a profound impact on human health and life quality. The treatment for HNC, especially for the advanced cancer is stage-dependent and in need of combined therapies. Various forms of adjuvant treatments such as chemotherapy, phototherapy, hyperthermia, gene therapy have been included in the HNC therapy. However, there are still restrictions with traditional administration such as limited in situ therapeutic effect, systemic toxicity, drug resistance, etc. In recent years, stimuli-responsive drug delivery systems (DDSs) have attracted the great attention in HNC therapy. These intelligent DDSs could respond to unique tumor microenvironment, external triggers or dual/multi stimulus with more specific drug delivery and release, leading to enhanced treatment efficiency and less reduced side effects. In this article, recent studies on stimuli-responsive DDSs for HNC therapy were summarized, which could respond to endogenous and exogenous triggers including pH, matrix metalloproteinases (MMPs), reactive oxygen species (ROS), redox condition, light, magnetic field and multi stimuli. Their therapeutic remarks, current limits and future prospect for these intelligent DDSs were discussed. Furthermore, multifunctional stimuli-responsive DDSs have also been reviewed. With the modification of drug carriers or co-loading with therapeutic agents. Those intelligent DDSs showed more biofunctions such as combined therapeutic effects or integration of diagnosis and treatment for HNC. It is believed that stimuli-responsive drug delivery systems showed great potential for future clinic translation and application for the treatment of HNC.